Groundwater Quality Protection : A Guide for Water Utilities, Municipal Authorities, and Environment Agencies - Foster, Stephen; Hirata, Ricardo; Gomes, Daniel; D'Elia, Monica; Paris, Marta (Washington, DC: World Bank, 2013)
This publication provides guidance to water-sector decision makers and planners on how to deal with the quality dimension of groundwater resources management in the World Bank's client countries. There is growing evidence of increasing pollution threats to groundwater and some well-documented cases of irreversible damage to important aquifers. This guide has been produced in the belief that groundwater pollution hazard assessment must become an essential part of environmental best practice for water supply utilities. The guide is particularly relevant for the World Bank's Latin American and Caribbean Region, where many countries have initiated major changes to modernize their institutional and legal framework for water resources management, but may not yet have considered groundwater at the same level as surface water, because of lack of awareness and knowledge of groundwater issues and policy options.